Effects of Trigger Point Dry Needling on Neuromuscular Performance and Pain of Individuals Affected by Patellofemoral Pain: A Randomized Controlled Trial [Corrigendum] - Ma YT (Journal of Pain Research, 2020)
Ma YT, Li LH, Han Q, et al. J Pain Res. 2020;13:1677–1686. The authors have advised Figure 3 on page 1682 is incorrect. Due to an error at the time of figure assembly Figure 2 and Figure 3 were duplicated. The correct Figure 3 is shown below. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article